A socially inclusive teaching strategy for transforming the teaching of English first additional language - M. L. Malebese (Perspectives in Education, 2018)
This paper explores ways of including indigenous knowledge systems in the teaching of English First Additional Language (EFAL). The aim is to use a socially inclusive teaching strategy in such a manner that the imbalances that past oppressive regimes brought into the teaching and learning of a second language, EFAL in this case, is challenged and possibly reversed. A desperate need for basic educational resources understandably warrants the promotion of a culture that is conducive to learning. Lacking resources are not limited to teacher knowledge, as can be gleaned from schools situated in rural settings. Undesirable cultures and conditions not conducive to learning prevail at the expense of hope and socially just educational practices. Indigenous knowledge systems and community cultural wealth, embedded in rural settings, are often underplayed and ignored. However, if incorporated in the teaching and learning process, they can create a familiar learning environment. In this paper, a socially inclusive teaching strategy was found to be helpful in ensuring the sustenance of transformation of learning while simultaneously contributing to the transformation of teaching English first additional language. This transformative charter of the paper warrants the framing of critical emancipatory research (CER) while adapting participatory action research principles to engage those affected by the problem and to determine solutions captured through meetings, workshops, document analysis, focus groups discussions and observations. The conversations were audio- and videotaped for the purpose of data analysis at the later stage. The reflections that permeate the analytic, interpretive and educative phases of CER, discourses that were subjected to van Dijk’s socio-cognitive critical discourse analysis, were found to be very helpful. Research findings confirm the two-way relationship between the availability of educational resources and learner attainment.